Pengaruh Edukasi Audiovisual terhadap Tingkat Pengetahuan dan Sikap Remaja tentang Kesehatan Reproduksi di SMA Islam Sultan Agung 3 - Dea Ajeng Nanda Liana Putri; Tutik Rahayu; Sri Wahyuni (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Education is necessary to address the low level of teenage understanding on reproductive health. This affects unintended pregnancies, abortions, IMS/PMS, and HIV/AIDS. This study set out to ascertain how offering audiovisual education packages affected the degree of teenage knowledge and attitudes about reproductive health at SMA Sultan Agung Islamic 3. This research is a quantitative research with a pre-experiental approach. The design of this research uses one group pretest-posttest design. Data collection was done by questionnaire. The number of respondents was 79 with random sampling method. The data obtained were processed statistically using the Wilcoxon formula. Based on the result of the analysis, the majority of 79 respondents had 100% characteristics of 10-18 years with 54,4% female gender and 45,6% male gender. The research result that before being given the audiovisual education package, 59,3% of respondents possessed adequate knowledge, 36.7% possessed strong knowledge, and 3.8% possessed inadequate knowledge. After being given the audiovisual education package, overall respondents fell into the 100% good knowledge category. Before being given the audiovisual education package, 63,3% of respondents had attitudes in the negative group, but all responder attitudes fell into the positive category after receiving the audiovisual education package. Providing audiovisual education packages has an impact on teenagers' reproductive health knowledge and attitudes (p value=0,000 <0.05 with a Z value of knowledge -5.444 and attitude -7.071).